2007
DOI: 10.1038/sj.ijir.3901615
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of sexual dysfunctions in male partners of women with vaginismus in a Turkish sample

Abstract: The aim of this investigation is to determine the sexual history traits, sexual satisfaction level and frequency of sexual dysfunctions in men whose partners have vaginismus. The study included 32 male partners of vaginismic patients, who presented at a psychiatry department. Subjects were evaluated by a semi-structured questionnaire. The questionnaire was developed by researchers for assessing sexually dysfunctional patients and included detailed questions with regard to sociodemographic variables, general me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
38
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 14 publications
(13 reference statements)
7
38
0
Order By: Relevance
“…Vaginismus is one such psychosomatic disorder of the female partner which precludes the intravaginal deposition of sperm. Such cases may frequently present with nonconsummation of marriage, dyspareunia, and infertility, and with secondary erectile dysfunction in the male partner (4)(5)(6)(7). The incidence of vaginismus varies from 2% in the general population to 47% in sex therapy clinics (8)(9)(10)(11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Vaginismus is one such psychosomatic disorder of the female partner which precludes the intravaginal deposition of sperm. Such cases may frequently present with nonconsummation of marriage, dyspareunia, and infertility, and with secondary erectile dysfunction in the male partner (4)(5)(6)(7). The incidence of vaginismus varies from 2% in the general population to 47% in sex therapy clinics (8)(9)(10)(11).…”
mentioning
confidence: 99%
“…In unconsummated marriages, vaginismus is reported to be the reason in 20% to 67% (7,24), and male sexual dysfunction commonly accompanies vaginismus (7). Counseling and treatment of the male partner is a very important aspect of management for these couples.…”
mentioning
confidence: 99%
“…25 A Turkish study conducted at a psychiatry department reported that the most common problem in males with vaginismic partners was premature ejaculation (50%). 26 The authors concluded that the increased rate in premature ejaculation was related to the interaction with the vaginismic wife. Although our survey reiterated the results of previous clinical research, we did not collect data regarding the primary appointment causes of neither women nor men.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is the lack of assessment of the quality of the patients' relationship with their partners. [33][34][35] These aspects together to the relationships among female sexuality, emotional regulation and other gynaecological disorders are currently being examined in our laboratory.…”
Section: Discussionmentioning
confidence: 99%